DEFINING THE ADDRESSING TERMS IN INDONESIAN LANGUAGE (A CASE STUDY OF GORONTALESE) - Olii, Sanerita Tresnawaty (Jurnal Pendidikan Bahasa Inggris undiksha, 2021)
As one aspect of sociolinguistics, social communication is used to indicate relationships in society and refers to names that may come from status. Indonesia has many regional languages, one of which is Gorontalo. In Gorontalo, there are many regional languages. This study aims to analyze the meaning of the greeting terms used by the Gorontalo language speakers. The qualitative descriptive method was used in this study through interviews. Informants were taken based on the criteria of native speakers, adults, able to speak and understand the language, good speaking skills, and socially acceptable groups. The data collection uses a list of words and sentences about the term nicknames in Indonesian as an instrument. The steps to analyze the data are unitization, categorization, explanation, and interpretation. The study results found several greeting terms in the Gorontalo language, namely community, and religious leaders, grandparents' relationships with parents, grandchildren, neighbors, and friends. The greeting terms here are used in the formal and informal language during a conversation, and each language that exists in different or different communication has its characteristics in using the greeting term.